Intelligent-Contextual Model for the Classification of Internet of Things Environments - Pidlisnyi, Yu.; Підлісний, Ю. І. (ЦНТУ, 2025)
This paper presents an intelligent-contextual model for classifying Internet of Things (IoT) environments, based on the comprehensive consideration of key parameters such as the level of embedded intelligence, operational context, security level, and system dynamics. The relevance of the study stems from the rapid growth in the complexity of IoT ecosystems, which are characterized by heterogeneous devices, diverse operating conditions, the need for adaptability to environmental changes, and increased security requirements. A critical analysis of existing IoT classification approaches reveals their major limitations: a narrow focus on purely technical or functional features, inadequate reflection of device behavior and intelligence, and the disregard for operational context and threat landscape etc. У статті представлено інтелектуально-контекстну модель класифікації середовищ Інтернету речей (IoT), яка ґрунтується на комплексному врахуванні ключових параметрів, таких як рівень вбудованого інтелекту, контекст функціонування, рівень безпеки та динамічність системи. Актуальність дослідження зумовлена стрімким зростанням складності екосистем IoT, що характеризуються гетерогенністю пристроїв, різноманітністю умов експлуатації, необхідністю адаптації до змін у навколишньому середовищі та підвищеними вимогами до безпеки. Критичний аналіз існуючих підходів до класифікації IoT виявив їхні основні обмеження: вузьку орієнтацію виключно на технічні або функціональні ознаки, недостатнє врахування поведінкових характеристик та інтелекту пристроїв, а також ігнорування контексту функціонування та ландшафту кіберзагроз тощо.
Інтелектуально-контекстна модель класифікації середовищ інтернету речей
Keywords: Internet of Things; IoT classification; intelligent systems; security; інтернет речей; класифікація IoT; інтелектуальні системи; безпека